2023
DOI: 10.1001/jamanetworkopen.2022.53692
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Hospital Frailty Risk Score and the Clinical Frailty Scale Among Older Adults With Chronic Obstructive Pulmonary Disease Exacerbation

Abstract: ImportanceFrailty is associated with severe morbidity and mortality among people with chronic obstructive pulmonary disease (COPD). Interventions such as pulmonary rehabilitation can treat and reverse frailty, yet frailty is not routinely measured in pulmonary clinical practice. It is unclear how population-based administrative data tools to screen for frailty compare with standard bedside assessments in this population.ObjectiveTo determine the agreement between the Hospital Frailty Risk Score (HFRS) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“… 32 The frailty status based on the FRAIL scale indicated that frailty was prevalent in these patients (85.7%), with 40.7% pre-frail and 45.0% frail. This result is consistent with the results of the study by Chin et al, 33 who used the Clinical Frailty Scale (CFS) to detect frailty in 86% of such patients included in their study, which is higher than the patients with COPD. In addition, the results of two previous studies 7 , 10 on patients hospitalized with AECOPD revealed that the incidence of COPD exacerbations in frail individuals was 42% higher than that in non-frail individuals (incidence rate ratio [IRR] 1.42, 95% CI 0.94–2.17).…”
Section: Discussionsupporting
confidence: 91%
“… 32 The frailty status based on the FRAIL scale indicated that frailty was prevalent in these patients (85.7%), with 40.7% pre-frail and 45.0% frail. This result is consistent with the results of the study by Chin et al, 33 who used the Clinical Frailty Scale (CFS) to detect frailty in 86% of such patients included in their study, which is higher than the patients with COPD. In addition, the results of two previous studies 7 , 10 on patients hospitalized with AECOPD revealed that the incidence of COPD exacerbations in frail individuals was 42% higher than that in non-frail individuals (incidence rate ratio [IRR] 1.42, 95% CI 0.94–2.17).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the HFRS does not account for the severity of comorbidities and does not consider the functional status and abilities of the patient, which are important aspects of frailty assessment. Interestingly, this was demonstrated in a recent cross‐sectional study in patients with COPD exacerbations that showed disagreement between the HFRS and CFS in categorizing frail patients 35 . We were only able to capture the functional baseline of 30% of the study population owing to insufficient data, making correlations between HFRS and function difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, this was demonstrated in a recent cross-sectional study in patients with COPD exacerbations that showed disagreement between the HFRS and CFS in categorizing frail patients. 35 We were only able to capture the functional baseline of 30% of the study population owing to insufficient data, making correlations between HFRS and function difficult.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HRFS relies heavily on acute diagnoses (eg, acute kidney failure or hypotension); the CFI-Kim includes infectious diseases (eg, pneumonia and influenza), lacerations, and paternity tests 33 ; and both the CFI-Segal and VA-FI include comorbidities (eg, hypertension and hyperlipidemia) highly prevalent in robust populations and not particular to frailty. As such, the face validity of these tools can be challenged, and these inconsistencies may explain their poor performance in specific disease states and among those that are critically ill. 39 , 40 Furthermore, the excellent discrimination of the HRFS for in-hospital mortality in the NIS may, in fact, highlight the tool’s selection of highly morbid, acute conditions without necessarily demonstrating specificity for frailty. For example, a 25-year-old professional athlete who slips on their stairs at home and falls again upon getting up with a resulting concussion and small traumatic intracranial hemorrhage would obtain an HFRS score consistent with frailty despite being an elite athlete (eMethods in Supplement 1 ).…”
Section: Discussionmentioning
confidence: 99%